2020
DOI: 10.3390/app10082741
|View full text |Cite
|
Sign up to set email alerts
|

Linear Accuracy of Full-Arch Digital Models Using Four Different Scanning Methods: An In Vitro Study Using a Coordinate Measuring Machine

Abstract: Improving the accuracy of the digital model is essential for the digitalization of the dental field. This study introduced a novel method of objective accuracy evaluation of digitized full dental arch model using coordinate measuring machine (CMM). To obtain a true linear measurement value using the CMM, 17 reference balls were attached to the typodont, and 12 measurements between balls on the X-(width), Y-(length), and Z-axes (height) were performed automatically. A rubber impression and a plaster cast replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
(52 reference statements)
3
10
0
Order By: Relevance
“…A general "shrinkage" of the digitalized models was observed after scanning comparing to the reference model (Table 1 and Table 2). This fact was also reported in previous studies [25,70,71] and researchers suggested that this tendency of "downsizing" of the digital models might be due to the algorithms used in the conversion software [71,72]. Digital models with statistically significant smaller measurements than the true measurements were also obtained by Kim et al who used for digitalization of plaster models intraoral scanners, desktop scanners and CBCT scan [25], downsized virtual models being obtained with all digitalization techniques.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…A general "shrinkage" of the digitalized models was observed after scanning comparing to the reference model (Table 1 and Table 2). This fact was also reported in previous studies [25,70,71] and researchers suggested that this tendency of "downsizing" of the digital models might be due to the algorithms used in the conversion software [71,72]. Digital models with statistically significant smaller measurements than the true measurements were also obtained by Kim et al who used for digitalization of plaster models intraoral scanners, desktop scanners and CBCT scan [25], downsized virtual models being obtained with all digitalization techniques.…”
Section: Discussionsupporting
confidence: 69%
“…This fact was also reported in previous studies [25,70,71] and researchers suggested that this tendency of "downsizing" of the digital models might be due to the algorithms used in the conversion software [71,72]. Digital models with statistically significant smaller measurements than the true measurements were also obtained by Kim et al who used for digitalization of plaster models intraoral scanners, desktop scanners and CBCT scan [25], downsized virtual models being obtained with all digitalization techniques. However, it should be note that, in the present study, when AAP was used as impression material, the errors were "compensated" and the obtained digital model was not statistically significant different to the reference model, in all measured parameters (Table 3).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations